(untitled) (London Journal of Engineering Research, 2024)
The emergence of a time-constant interaction force between a pair of antennas of sound and electromagnetic waves is shown analytically. This force is identically analytically expressed through the phases of excitation of the antennas and the distance between them both for acoustic and electromagnetic cases. Frequencies, excitation phases, and distances between the antennas were found at which the antennas maximize either the mutual repulsive (attractive) forces in a pair of antennas, or the wave thrust forces that tend to move a pair of antennas in one direction. It is shown that the force of the wave thrust of a pair of antennas is opposite to the radiation flux, which plays a role similar to gases flowing from a rocket nozzle. For a catamaran (two floats-antennas of surface gravity waves on water with a phase shift of their vertical oscillations by ) the forward motion speed and the force of wave thrust, as well as the surface jet current near the float, similar to the flow created by a propeller, were measured. In this case, the inversion of the difference in the excitation phases of the half floats simultaneously led to an inversion of the thrust force, translational motion and jet flow. The dependence of the wave thrust on the excitation frequency (with a structurally fixed phase difference ) in the experiment turned out to be similar to the analytically obtained dependences for sound and electromagnetic waves.